Effects of honey use on the management of radio/chemotherapy-induced mucositis: a meta-analysis of randomized controlled trials. Issue 12 (December 2016) - Xu, J.-L.; Xia, R.; Sun, Z.-H.; Sun, L.; Min, X.; Liu, C.; Zhang, H.; Zhu, Y.-M.
Abstract: This meta-analysis aimed to assess the prophylactic effects of honey use on the management of radio/chemotherapy-induced mucositis. PubMed, Cochrane Library, Science Direct, China National Knowledge Infrastructure (CNKI), VIP (Chinese scientific journal database), and China Biology Medicine (CBM) were searched for relevant articles without language restriction. Two reviewers searched and evaluated the related studies independently. Statistical analyses were performed using Stata 11.0, calculating the pooled risk ratio (RR) with the corresponding 95% confidence interval (CI). Begg's funnel plot was used together with Egger's test to detect publication bias. A total of seven randomized controlled trials were finally included. Quality assessment showed one article to have a low risk of bias, two to have a moderate risk, and four to have a high risk. Meta-analysis showed that, compared with blank control, honey treatment could reduce the incidence of oral mucositis after radio/chemotherapy (RR 0.35, 95% CI 0.18–0.70, P  = 0.003). No meta-analysis was applied for honey vs. lidocaine or honey vs. golden syrup. The sensitivity analysis showed no significant change when any one study was excluded. No obvious publication bias (honey vs. blank control) was detected. In conclusion, honey can effectively reduce the incidence of radio/chemotherapy-induced oral mucositis; however, further multi-centre randomized controlled trials are needed to support the current evidence.